Entrepreneurs’ And Customers’ Engagement, Motivation And Satisfaction Towards Online Video-based Training And Advertisement - Mohd Dahlan, Mariani (2021)
This research emerged from the researcher‟s concern and reviews on the weaknesses of the Bumiputera Small Medium Enterprises, SME entrepreneurs in marketing and network business. The purpose of this research is to explore the entrepreneurs‟ and customers‟ engagement, motivation and satisfaction towards online video-based training and advertisement. The participants were chosen from the new MARA SMEs in Perak and the chosen research method was a mixed-method sequential explanatory design involving quantitative and qualitative methods. The independent variables were video-based Facebook training (vFB-Ads) and FB Advertisement (FB Ads). The dependent variables involved the entrepreneurs‟ learning engagement, perceived motivation, and satisfaction as well as their customers‟ engagement and satisfaction of the vFB-Ads and FB Ads. A total of 31 entrepreneurs were randomly sampled from MARA Negeri Perak. The data obtained were analysed by carrying out descriptive and inferential statistics, as well as thematic analysis. The findings obtained from the analysis of the entrepreneurs‟ learning engagement towards vFB-Ads revealed that they indicate the emotional, behavioural and cognitive engagement towards vFB-Ads. Likewise, in terms of the entrepreneurs‟ perceived motivation, it also revealed that the vFB-Ads attract their attention and the vFB-Ads were relevant to them.